Low-Temperature Technologies and Applications - Newaz Kazi, Salim (IntechOpen, 2022)
This book on low-temperature technology is a notable collection of different aspects of the technology and its application in varieties of research and practical engineering fields. It contains, sterilization and preservation techniques and their engineering and scientific characteristics. Ultra-low temperature refrigeration, the refrigerants, applications, and economic aspects are highlighted in this issue. The readers will find the low temperature, and vacuum systems for industrial applications. This book has given attention to global energy resources, conservation of energy, and alternative sources of energy for the application of low-temperature technologies.